IGF-1 in Friedreich’s Ataxia – proof-of-concept trial - Sanz-Gallego, Irene (Cerebellum Ataxias, 2014)
BACKGROUND: Friedreich’s ataxia is an autosomal recessive, severely incapacitating disorder. There is little objective evidence regarding FRDA management. Abnormalities in the insulin/insulin-like growth factor 1 (IGF-1) system (IIS) signalling pathway were thought to play a role in the physiopathological processes of various neurodegenerative disorders, including spinocerebellar ataxias. The objective of the study was to test the safety, tolerability, and efficacy of therapy with IGF-1 in Friedreich’s ataxia (FRDA) patients in a clinical pilot study. RESULTS: A total of 4 females and 1 male were included in the study; 23 to 36 years of age (average 26.6 ± 5.4), diagnosed with FRDA with normal ventricular function. Patients were treated with IGF-1 therapy with 50 μg/kg twice a day subcutaneously for 12 months. The efficacy of this therapy was assessed by changes from baseline on the scale for the assessment and rating of ataxia, (SARA) and by changes from baseline in echocardiogram parameters. The annual worsening rate (AWR) was estimated in this series as a SARA score of -0.4 ± 0.83 (CI 95%: -1.28 to 0.48) SARA score, whereas the AWR for our FRDA cohort was estimated as a SARA score of 2.05 ± 1.23 (CI 95%: 1.58 to 2.52). Echocardiographic parameters remained normal and stable. CONCLUSION: Our results seem to indicate a benefit of this IGF-1 therapy to neurological functions in FRDA.